Changes in Metabolism and Proteostasis Drive Aging Phenotype in Aplysia californica Sensory Neurons - Kron, Nicholas S.; Schmale, Michael C.; Fieber, Lynne A. (Frontiers in Aging Neuroscience, 2020)
Aging is associated with cognitive declines that originate in impairments of function in the neurons that make up the nervous system. The marine mollusk Aplysia californica (Aplysia) is a premier model for the nervous system uniquely suited to investigation of neuronal aging due to uniquely identifiable neurons and molecular techniques available in this model. This study describes the molecular processes associated with aging in two populations of sensory neurons in Aplysia by applying RNA sequencing technology across the aging process (age 6–12 months). Differentially expressed genes clustered into four to five coherent expression patterns across the aging time series in the two neuron populations. Enrichment analysis of functional annotations in these neuron clusters revealed decreased expression of pathways involved in energy metabolism and neuronal signaling, suggesting that metabolic and signaling pathways are intertwined. Furthermore, increased expression of pathways involved in protein processing and translation suggests that proteostatic stress also occurs in aging. Temporal overlap of enrichment for energy metabolism, proteostasis, and neuronal function suggests that cognitive impairments observed in advanced age result from the ramifications of broad declines in energy metabolism.